ANALISIS PERBEDAAN OVERLAP CAMSHAFT DURATION TERHADAP DAYA DAN TORSI SEPEDA MOTOR SATU SILINDER 110 CC: ANALYSIS OF THE DIFFERENCES OVERLAP CAMSHAFT DURATION ON POWER 110 CC ONE CYLINDER MOTORCYCLE - Nurfirmansyah, Muhammad; Ahmad Hanif Firdaus (Jurnal Teknik Mesin, 2025)
The decline in performance of a vehicle that has been used for a long time makes it less comfortable when used. The aim of this research is to determine the results of the effect of camshaft overlap duration on the power of a 110 cc petrol engine. To verify its performance, experimental research methods were used in this thesis research. The research results show that varying the duration of camshaft overlap has the effect of increasing vehicle power. For example, using a variation of the camshaft overlap duration of 38o produces the highest power with 7.45 (Hp) at an engine speed of 7000 rpm. This can happen because according to the theory that the greater the duration of the camshaft overlap on a vehicle, the better the flushing of the combustion chamber at top speed.